(untitled) (Journal of the College of Education for Women, 2019)
The Risks Faced by Britain in their Areas of Influence at the Beginning of the Twentieth Century Drove her to the Alliance with the State of European such as France, and Contributed to the Tireless and made by the British and French Politicians in the Consolidation of Friendly Relations between the two Countries Efforts and Strengthened Cooperation in a Positive Way to Visit the king of Britain’s Edward VII to France, Offset by Visit French President Loubet to Britain in the Same Year, those Negotiations Bore Fruit between the two Countries for Reaching a Contract Arbitration and Decisiveness between Britain and France Treaty on the Fourteenth of November 1903, Promised that Treaty First Step that Paved the Way for a General Agreement between the two Countries, Marked by the Holding of Reconciliation Friendly on the eighth of April 1904.